The supernova remnant SN 1006 as a Galactic particle accelerator - Roberta Giuffrida; Marco Miceli; Damiano Caprioli; Anne Decourchelle; Jacco Vink; Salvatore Orlando; Fabrizio Bocchino; Emanuele Greco; Giovanni Peres (Nature Communications, 2022)
It is known that cosmic rays could be accelerated by shock waves in supernova (SN) remnants. Here, the authors show that SN 1006 remnant is an efficient source of cosmic rays, providing observational support for the quasi-parallel acceleration mechanism.